Primary failure of eruption: From molecular diagnosis to therapeutic management - Delphine Wagner; Tristan Rey; Marie-Cécile Maniere; Sarah Dubourg; Agnès Bloch-Zupan; Marion Strub (Elsevier, 2023)
Introduction: Primary Failure of Eruption (PFE) is a rare condition affecting posterior teeth eruption resulting in a posterior open bite malocclusion. Differential diagnosis like ankylosis or mechanical eruption failure should be considered. For non-syndromic forms, mutations in PTH1R, and recently in KMT2C genes are the known etiologies. The aim of this work was to describe the variability of clinical presentations of PFE associated with pathogenic variants of PTHR1. Material and methods: Diagnosis of non-syndromic PFE has been suggested for three members of a single family. Clinical and radiological features were collected, and genetic analyses were performed. Results: The clinical phenotype (type and number of involved teeth, depth of bone inclusions, functional consequences) is variable within the family. Severe tooth resorptions were detected. A heterozygous substitution in PTH1R (NM_000316.3): c.899T > C was identified as a class 4 likely pathogenic variant. The multidisciplinary management is described involving oral biology, pediatric dentistry, orthodontics, oral surgery, and prosthodontics. Conclusion: In this study, we report a new PTH1R variant involved in a familial form of PFE with variable expressivity. Therapeutic care is complex and difficult to systematize, hence the lack of evidence-based recommendations and clinical guidelines.